2020
DOI: 10.1111/cns.13283
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural disruption of the right inferior fronto‐occipital and inferior longitudinal fasciculus contributes to WMH‐related cognitive impairment

Abstract: Aims: White matter hyperintensity (WMH) is the most common neuroimaging manifestation of cerebral small vessel disease and is related to cognitive dysfunction or dementia. This study aimed to investigate the mechanism and effective indicators to predict WMH-related cognitive impairment. Methods:We recruited 22 healthy controls (HC), 25 cases of WMH with normal cognition (WMH-NC), and 23 cases of WMH with mild cognitive impairment (WMH-MCI). All individuals underwent diffusion tensor imaging (DTI) and a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 61 publications
5
68
1
Order By: Relevance
“…An experienced neuropsychologist conducted all the testing. The raw scores were transformed to Z-scores for each test [30,31], which could be computed as follows:…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…An experienced neuropsychologist conducted all the testing. The raw scores were transformed to Z-scores for each test [30,31], which could be computed as follows:…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…Previous studies by resting-state MRI have demonstrated that disrupted nodal topological properties are strongly correlated with WMH related CI (40,41). In terms of the white matter network, WMH can disrupt the integrity of white matter fibers and damage structural connections (42,43), resulting in disrupted topological properties of nodes connected by the white fibers. Our study indicated that altered NLp and nodal efficiency in most regions are associated with WMH location and CI.…”
Section: Discussionmentioning
confidence: 97%
“…We found only NLp in IFGoperc.L significantly mediated in PWMH-related memory deficit rather than DWMH. A recent study suggested that WMH can disrupt the left inferior fronto-occipital fasciculus which is one of the connections of the left inferior frontal gyrus (43). PWMH is more likely to disrupt white matter microstructure than DWMH.…”
Section: Discussionmentioning
confidence: 99%
“…Myelinated WM tracts are responsible for long‐range connectivity through axonal transport, and their lesions can lead to neuronal circuits processing speed deficits and corticocortical disconnections 23 . The pathological changes in WM can predict VCID according to neuropathology guidelines, and WM injury is a significant contributor to dementia 24‐26 …”
Section: Overview Of Vascular Cognitive Impairment and Dementia (Vcid)mentioning
confidence: 99%